Incidence of anaphylaxis and accidental peanut exposure: A systematic review. Issue 8 (6th October 2021) - Muraro, Antonella; Sublett, J. Wesley; Haselkorn, Tmirah; Nilsson, Caroline; Casale, Thomas B.
Abstract: Background: Peanut allergy (PA), a common food allergy, is increasing in prevalence and is associated with high rates of anaphylaxis. Prevalence of food‐related anaphylaxis is higher in children and adolescents than in adults, and the pediatric incidence is increasing. We conducted a systematic literature review and meta‐analysis to determine the incidence of peanut‐induced anaphylaxis in children and/or adolescents with PA. Methods: Literature searches were conducted using the PubMed database and through supplemental methods. Eligible articles for inclusion were peer‐reviewed studies published in English that reported the incidence of anaphylaxis in pediatric PA using the 2006 National Institute of Allergy and Infectious Disease/Food Allergy and Anaphylaxis Network criteria, sample size, and follow‐up duration. Incidence rates were calculated as person‐years at risk or a crude incidence rate was calculated. Meta‐analyses of pooled data were conducted using the I 2 statistic as the measure of heterogeneity. Results: A total of 830 citations were screened; 8 met the study inclusion criteria and were selected for review. Pooled meta‐analysis estimates of the incidence of (1) anaphylaxis among children/adolescents with food allergies, (2) anaphylaxis among children/adolescents with PA, and (3) accidental exposure to peanuts among children/adolescents with PA were 3.72 cases per 100 person‐years (95% confidence interval [CI] = 2.35, 5.10), 2.74 cases per 100 person‐years (95% CI = 1.42, 4.05), and 12.28 cases per 100 person‐years (95% CI = 11.51, 13.05), respectively. Conclusions: The risks of anaphylaxis among children with food allergies and those with PA contribute to the serious overall burden of PA and food allergy for children and their families.